Neurophysiology for Detection of High Risk for Psychosis. (7th August 2016) - Pantlin, Lara N.; Davalos, Deana
Abstract : Schizophrenia is a complex and often disabling disorder that is characterized by a wide range of social, emotional, and cognitive deficits. Increasing research suggests that the greatest social and cognitive therapeutic impact comes from early identification. The present study applied a well-established neurophysiological paradigm in the schizophrenia literature, mismatch negativity (MMN), to college students identified as high risk (HR) for psychosis to investigate MMN as a potential biomarker for the onset of psychosis. The hypothesis was that HR would exhibit attenuated MMN amplitudes compared to controls, as has been established in individuals with chronic schizophrenia. Participants (N = 121 ) were separated into Group 1 (controls) (n 1 = 72 ) and Group 2 (HR) (n 2 = 49 ) based on the established cutoff score of the 16-item Prodromal Questionnaire. Participants then completed a time based MMN paradigm during which brain activity was recorded with EEG. For all electrode locations, controls demonstrated significantly more negative amplitudes than HR (C z : F ( 1, 119 ) = 8.09, p = . 005 ; F z : F ( 1, 119 ) = 5.74, p = . 018 ; P z : F ( 1, 119 ) = 5.88, p = . 017 ). Results suggested that MMN may assist in identifying those who appear high-functioning but may be at risk for later development of psychosis or cognitive and psychological difficulties associated with psychosis.